A crítica de cinema como gênero discursivo jornalístico: um estudo de caso a partir de Bacurau - Rocha, Vinícius Oliveira (2023)
The present work seeks to address film criticism as a journalistic discursive genre and how its discursive constructions, along with the repertoires and references possessed by the critic (including geocultural ones), seek to legitimize his position in his process of film analysis. For this, a set of reviews of the film Bacurau (2019) written in Portuguese, English and French was determined as the research object. The adopted literature initially traced a historical path of criticism, presenting the main milestones and transformations experienced by it at an international and national level, and also bringing the challenges and clashes faced by critics in the digital environment. Then, a proposal was brought to correlate the Order of Discourse, as presented by Michel Foucault, with the construction processes of critical discourse. For the analysis of the reviews, the methodology was constructed based on the Thematic Analysis, and the collection and analysis of the contents identified in these criticisms sought first to work them separately by language and then comparatively. The results show that most critics see geographical and political themes in Bacurau, linking them to their cinematographic and cultural repertoires, allowing them to make connections between the film and film works by other directors and cinematographic genres such as the western. At the same time, the subjectivities of these critics emerged from the discourses produced about the film, allowing to identify substantial differences in their analyzes depending on their geocultural references, while their repertoires helped to outline common elements to the formation of the critic and the production of his discourse even in different parts of the world.